Analysis of Framing Political Dynasty News Post-Constitutional Court Decision on Online Media CNN Indonesia and Detik.Com.: Islamic Perspective in Political Criticism - Mukhlizar, Mukhlizar; Vahlevi, Randy Reza (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
This study aims to analyze the framing of dynastic political news on online media CNN Indonesia and Detik.com by using qualitative research methods. By conducting a framing comparison between CNN Indonesia and Detik.com, this research reveals how the two media influence public perceptions of dynastic politics, as well as how Islam views some of the Issues listed in the news. The results show that CNN Indonesia tends to emphasize the legal aspects and social impacts of dynastic politics by focusing on moral judgments about the Constitutional Court's decision where the moral value is contained in (Q.S. Al-Ma'aarij: 32). Meanwhile, Detik.com highlights the political dynamics and figures involved in dynastic politics, with an emphasis on personal narratives, namely assessments related to the ability to lead. In Islam, the ability to lead must be based on moral values, wisdom, and the ability to be an example.